A Case of External Ophthalmomyiasis in a Deployed UK Soldier. Issue 1 (1st March 2008) - Stacey, Mike; Blanch, RJ
Abstract : Infestation of the eye by larval fly forms (ophthalmomyiasis) is rarely seen in the Western world. We present the case of a 21 year old British soldier who developed external ophthalmomyiasis during an operational tour of southern Afghanistan. This case report and discussion illustrates the potential for ophthalmomyiasis in personnel deployed to this theatre; the possibility of infestation without an identifiable episode of exposure; the importance of proper assessment and follow-up in order to identify sight-threatening complications; and the balance between optimal patient care and the risks inherent to casualty evacuation demanded by modern day stability operations.